Information behaviour: Graduates' pattern in seeking for information - Mohd Nadzir, Maslinda (2013)
Past researches on students' information seeking behaviour concluded that some students having difficulty in searching for information and unavailable to find the required information during the searching processes.The problem must be addressed as students need exposure on the knowledge of information searching and retrieval.This study explores graduate students' information seeking behaviour in seeking for information with the intention of accomplishing their research tasks.The data was collected through survey method by using web based questionnaire.A total of 193 respondents have responded to the survey questionaire.The collected data was analyzed by using Statistical Package for Social Sciences (SPSS) for Windows version 12.0.The findings of this study conclude that most of the graduate students prefer to use electronic information sources when seeking for research information.It can be use as guideline to improve information services and facilitate graduate students to construct better information search strategies during information seeking information seeking activities in finding the relevant research information effectively.